2015
DOI: 10.19041/apstract/2015/1-2/1
|View full text |Cite
|
Sign up to set email alerts
|

Financing and operating questions of sports facilities

Abstract: This paper tends to present financing and operating questions of sports facilities. Infrastructure is very important for the sport businesses. Sports facilities and sports institutions, infrastructure development, and their legal, financial, accounting conditionality can be defined by the investors and the government (subsidies, taxes, etc.). Financial questions and IT background of facility management can be crucial for the enterprises interested in operating sports businesses. The paper focuses on these kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…One of the most important factors affecting the return of citizens to the countryside is the availability of the sports infrastructure and the functioning of the local sports associations, sport clubs as it was reported in Hungary. The availability of this infrastructure and these services depends on the support of the government and of the local authorities [98]. The sport clubs are mostly civil associations operating in a non-profit framework but in the case of professional sport the presence of for-profit companies is getting more and more important both in Hungary and Germany as well [99].…”
Section: The Role Of the Countryside In The Health Promotionmentioning
confidence: 99%
“…One of the most important factors affecting the return of citizens to the countryside is the availability of the sports infrastructure and the functioning of the local sports associations, sport clubs as it was reported in Hungary. The availability of this infrastructure and these services depends on the support of the government and of the local authorities [98]. The sport clubs are mostly civil associations operating in a non-profit framework but in the case of professional sport the presence of for-profit companies is getting more and more important both in Hungary and Germany as well [99].…”
Section: The Role Of the Countryside In The Health Promotionmentioning
confidence: 99%
“…also stated that influencing factors showing regional or municipality based diversity of the macro environment of sport may also play a role such as economic power (GDP), settlement size composition, unemployment rate, but also geographical attributes and the number of sporting facilities. Kozma (2010a) found that sport also may play an effective tool in city marketing, furthermore the portfolio of sporting facilities at a region (Kozma, 2010b) ) and the financing structure of those facilities (Becsky et al, 2015) may influence sport participation of the local population. As mentioned more research data is available on the mentioned three approaches on both the European and national levels, but less that considering the regional characteristics of sport participation.…”
Section: Introductionmentioning
confidence: 99%